2005
DOI: 10.1177/10570837050140020108
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Certification Practices for Music Educators in the Fifty States

Abstract: Bruner (1977) observed that "Americans are a changing people; their geographical mobility makes imperative some degree of uniformity among high school and primary schools. Yet the diversity of American communities and of American life in general makes equally imperative some degree of variety" (p. 9). These observations also pertain to teacher credentialing practices in the United States. A mobile society will see not only students relocating from state to state, but teachers as well. While uniform teacher cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…The absence of statistically significant findings related to the influence of preservice education is worthy of further consideration by the field of music education. Preservice music education in the United States typically focuses on developing music educators prepared to teach K-12 (Henry, 2005) and thus programs must make choices about which grade levels or music content areas are prioritized in the curriculum. Yet, the absence of preservice as an influencer on how music educators teach middle school general music raises several questions for future research.…”
Section: Research Questionmentioning
confidence: 99%
“…The absence of statistically significant findings related to the influence of preservice education is worthy of further consideration by the field of music education. Preservice music education in the United States typically focuses on developing music educators prepared to teach K-12 (Henry, 2005) and thus programs must make choices about which grade levels or music content areas are prioritized in the curriculum. Yet, the absence of preservice as an influencer on how music educators teach middle school general music raises several questions for future research.…”
Section: Research Questionmentioning
confidence: 99%
“…Few studies have been conducted on music teacher certification practices across the 50 states and the District of Columbia, perhaps due to the difficulty of the data collection process (Dumas & Weible, 1984; Henry, 2005). In a 50-state study of elementary teacher certification, Dumas and Weible (1984) reported the necessity of making judgments about the exact nature of certification requirements despite repeated contact with state offices of education.…”
Section: Previous Reviews Of Music Teacher Certification Practicesmentioning
confidence: 99%
“…Teacher certification and licensure practices for music educators vary by state. Preservice music teachers, practicing music teachers, and music teacher educators can all benefit from knowledge of music teacher certification and licensure practices, as this knowledge can inform the quality of teacher preparation programs and teaching practices (Henry, 2005). An understanding of teacher certification and licensure practices can also help inform curriculum decisions for music teacher preparation programs and assist with student advisement specific to employment (Henry, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Music teacher education programs commonly include specialized coursework and a bachelor’s degree from an accredited institution, plus content examinations designed to ensure teacher readiness for the classroom (Elpus, 2015). Although these certification standards vary from state to state (Elpus, 2015; Ludlow, 2011), such criteria ultimately aim to promote consistency in quality across teacher preparation programs (Henry, 2005).…”
mentioning
confidence: 99%